2015
DOI: 10.1016/j.compag.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a 2D CFD model of the airflow produced by an airblast sprayer during pesticide treatments of citrus

Abstract: ElsevierSalcedo Cidoncha, R.; Granell Ruiz, R.; Palau-Salvador, G.; Vallet, A.; Garcerá, C.; Chueca, P.; Moltó, E. (2015). Design proposes and validates a two dimensional CFD model to be applied in citrus tree 19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
(3 reference statements)
0
13
0
3
Order By: Relevance
“…La precisión fue de 1.5 % con una resolución de 0, 01 m/s. En cada punto se registraron durante un minuto las tres componentes de la velocidad, margen de tiempo lo suficientemente largo para que las velocidades captadas representen el régimen estacionario en estas condiciones (Salcedo et al, 2015).…”
Section: Obtención De Los Datos Experimentalesunclassified
See 2 more Smart Citations
“…La precisión fue de 1.5 % con una resolución de 0, 01 m/s. En cada punto se registraron durante un minuto las tres componentes de la velocidad, margen de tiempo lo suficientemente largo para que las velocidades captadas representen el régimen estacionario en estas condiciones (Salcedo et al, 2015).…”
Section: Obtención De Los Datos Experimentalesunclassified
“…Existen publicaciones donde se aborda esta cuestión de forma descriptiva acompañada de ejemplos (Celik et al, 2008). En el caso de estudio, dicho análisis fue llevado a cabo en Salcedo et al (2015), por lo que, en coherencia con dicho trabajo, se recomienda adoptar directamente celdas de 4 cm de lado en la entrada de aire en el modelo y la zona de losárboles. En esa zona las celdas siguen una distribución uniforme.…”
Section: Malladounclassified
See 1 more Smart Citation
“…In agrochemical applications on orchards and vineyards, the idea of producing droplets by using nozzles and transporting them to vegetation, by using an air jet generated by a fan, is now the generally accepted method. Some studies [1][2][3][4][5][6] have demonstrated that stream speed strongly influences the effectiveness of spray treatment. If the speed is too low, the distribution of chemicals on vegetation tends to be non-uniform.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, if the speed is too high, the leaves align with the air stream, and much of the spray is not captured by the vegetation. Spray drift increases with velocity until approximately 50% of the spray does not land on the vegetation [3,4] and, consequently, causes both economic loss and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%